The welfare effects of financial inclusion in Ghana: An exploration based on a multidimensional measure of financial inclusion - Abdul Malik Iddrisu; Michael Danquah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Using a nationally representative household survey data set from Ghana, this paper provides empirical evidence regarding the role of financial inclusion or financial exclusion in household welfare. We first compute a multidimensional index of financial inclusion, and then we examine the effect of financial inclusion on household welfare. The study finds that households suffering financial deprivation have lower welfare compared with their financially included counterparts. Also, we observe that poor households experience much larger welfare effects of financial inclusion relative to non-poor households, indicating the potential of financial inclusion for reducing income inequality. Thus, policies that aim to deepen the extent of financial inclusion would be important in the quest to reduce the incidence of poverty and vulnerability as well as inequality.
Keywords: G21; I31; I32; 330; financial inclusion; financial exclusion; financial deprivation; household welfare; Ghana